Mechanism for Regulating Interactions Between Personality-Based Agents - Gonçalves, Luciano V.; Dimuro, Graçaliz P. (Proceedings of the Workshop-School on Agents, Environments, and Applications (WESAAC); 2007: Proceedings of the 1st Workshop-School on Agents, Environments, and ApplicationsDO - 10.5753/wesaac.2007.33035, 2007)
This work describes a simulator of social exchanges based on personality traits, with an associated regulation mechanism conduced by an equilibrium supervisor, where an agent is the manager of the social interactions that occur in the multiagent system. The implementation was done with the Jason Interpreter. We also present some simulation results of social exchanges between pairs of agents with different personality traits and obedience levels to the regulation mechanism.